Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) terhadap Peningkatan Kemampuan Kognitif Siswa - Hanna Florida Panjaitan; Anton Sitepu; Lasmaria Agnes Sinaga; Darinda Sofia Tanjung; Antonius Remigius (Universitas Serambi Mekkah, 2026)
This study aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning model on improving students' cognitive abilities in IPAS learning for fourth-grade students at SD UPT 064990 Medan Johor in the 2025/2026 academic year. This research employed a quantitative approach using an experimental method with a One Group Pretest-Posttest Design. The research sample consisted of 30 students selected through a total sampling technique. Data collection techniques included tests, questionnaires, and documentation. Data analysis was conducted through normality tests, Product Moment correlation tests, and hypothesis testing using the t-test. The results showed an increase in students' average scores from 46.83 in the pretest to 75.67 in the posttest. The correlation test obtained r = 0.665, indicating a strong relationship, while the t-test result showed tcount = 4.715 > ttable = 2.048, meaning that the alternative hypothesis was accepted. Therefore, the TGT cooperative learning model has a significant effect on improving students' cognitive abilities in IPAS learning.